Prioritizing User Requirements based on Analytic Hierarchy Process. Issue 1 (March 2021) - Tang, Jiahui
Abstract: As users have higher and higher requirements for products and competition in the product market becomes increasingly greater, how to use company resources more scientifically and quickly develop products that meet user needs becomes more and more important. Therefore, in this study, we apply the analytic hierarchy process for user requirement analysis, and clarify the advantages of the analytic hierarchy process compared with the existing commonly used models for prioritizing user needs and present the principles, methods, and results of the analytic hierarchy process in detail.